Capturing the ‘art’ of emergency medicine: Does film foster reflection in medical students? - Brand, G.; Wise, S.; Siddiqui, Z.; Celenza, A.; Fatovich, Daniel (Wiley-Blackwell Publishing Asia, 2017)
© 2017 Australasian College for Emergency Medicine and Australasian Society for Emergency Medicine Objective: Integrating arts and humanities-based pedagogy into curricula is of growing interest among medical educators, particularly how it promotes reflection and empathy. Our aim was to explore whether a 2.50 min film titled ‘The Art of the ED’ stimulated reflective learning processes in a group of first year medical students. Methods: The film was shown prior to their first clinical placement in an ED. Student participation was voluntary and not assessable. Using an exploratory qualitative research approach, this study drew on data collected from students’ individual written reflections, exploring their perceptions towards clinical experience in an emergency medicine (EM) attachment. Results: A total of 123 (51% of 240) students submitted a reflection. The qualitative data revealed three main themes: the opportunity for students to preview EM (‘While watching the film, I felt like I was the patient and the doctor all at once, in that I was living the experience both from within and as an observer …’); exposed the reality of ED; and fostered a growing awareness of the fragility of human life. Conclusions: These findings highlight how visual methodologies (like film) create a safe, non-threatening space to access, experience and process emotion around their perceptions towards EM, and to anticipate and emotionally prepare for their impending clinical experience in the ED. These data support the use of visual methodologies to foster reflective processes that assist medical students to integrate the ‘art’ of EM, and the development and commitment of core doctoring values of empathy, service and respect for patients.